2017
DOI: 10.1007/s11356-017-8910-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of highway traffic and the acoustic screen on the content and spatial distribution of heavy metals in soils

Abstract: Recent years have witnessed intensification of road traffic and, with it, the amount of substances emitted by vehicles. Such emissions need to be monitored for public health purposes. The aim of this study was to evaluate the impact of the highway traffic on the total content and bioavailability of Zn, Cu, Ni, Cd, Cr and Pb in nearby soils as well as influence of an acoustic screen on spatial distribution of the metals. The material included 40 soil samples collected from 15 research points located 5, 10, 25 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 44 publications
5
18
0
1
Order By: Relevance
“…The occurrence of unexpectedly higher concentrations of nickel at the railway station and on the west side of the study area may be related to its geochemical origin, as recorded in a previous study [48]. The Igeo values of class II (0-1) were found for Pb, Co, and Cr near the main city roads, possibly affected by heavy traffic [57][58][59][60].…”
Section: Maps Of Geo-accumulation Indexsupporting
confidence: 66%
“…The occurrence of unexpectedly higher concentrations of nickel at the railway station and on the west side of the study area may be related to its geochemical origin, as recorded in a previous study [48]. The Igeo values of class II (0-1) were found for Pb, Co, and Cr near the main city roads, possibly affected by heavy traffic [57][58][59][60].…”
Section: Maps Of Geo-accumulation Indexsupporting
confidence: 66%
“…The average ratio of the extractable concentration to total concentration, that is metal extractability, increased in the order Cr<Ni<Mn<Zn<Cu<Pb<Cd, being on average greater than 30 % for Cu, Pb, and Cd. In a recent study, Różański et al (2017) found that Pb was the most bioavailable and mobile element (mean PbDTPA 25.79 %).…”
Section: Chemical Availability Of Metals In Miraflores Garden Soilmentioning
confidence: 97%
“…Urban street dust is a heterogeneous mixture of particles coming from a variety of sources including automobile exhaust, atmospheric aerosols, industrial emissions, wear and tear on brakes and tires, soil erosion, weathering of building materials, and plant residue (Charlesworth et al 2003;Tervahattu et al 2006; Thorpe and Harrison 2008;Gunawardana et al 2012;Franco et al 2017;Men et al 2018). At the same time, street dust particles are a source of pollutants in roadside soils (Prokof'eva et al 2017;Ró _ zański et al 2017;Pariente et al 2019), which can re-enter the atmosphere through resuspension (Jordanova et al 2014) or migrate with surface runoff and stormwater (Calvillo et al 2015;Liu et al 2016). Numerous studies are devoted to the status of various pollutants, primarily PTEs and PAHs, in street dust in some of the world's largest megacities, industrial production centres (Liu et al 2007;Saeedi et al 2012;Acosta et al 2014;Yu et al 2014;Soltani et al 2015;Bandowe and Nkansah 2016;Tang et al 2017;Men et al 2018;Cappelletti et al 2019), cities, and towns (Majumdar et al 2017;Ghanavati et al 2019;Zhaoyong et al 2019).…”
Section: Introductionmentioning
confidence: 99%